Evaluation of Serum Interleukin-6 Levels in Correlation to the Severity of Acute Appendicitis - Al-Shahwany, Imad Wajeh; Kamal, Zuhair Bashir; Hindoos, Laith Naief h (AL-Kindy College Medical Journal, 2009)
Background: Acute appendicitis is a common surgicalproblem that is associated with an acute-phase reaction.Previous studies have shown that cytokines and acutephase proteins are activated and may serve as indicators forappendicitis.Objective: The aim of this study was to evaluate of serumlevels of interleukin-6 (IL-6) in correlation to the severityto acute appendicitis.Methods: This is a prospective study from December 2008to March 2009 of patients who had appendectomy inDepartment of Surgery, Al-Kindy Teaching Hospital -Baghdad/Iraq. Serum for estimating levels of interleukin-6(IL-6) was taken pre-operatively. Depending on themacroscopic evidence during the operation and thehistopathological examination of the specimens, thepatients were separated into 3 groups, group one withnegative appendectomy (normal appendix), group two withnon-complicated acute appendicitis (catarrhal,suppurative), and group three with complicated acuteappendicitis (perforated, gangrenous). Thehistopathological results were correlated with IL-6 valuesstatistically.Results: A total number of 50 patients were included inthis study, 28 male (56%) and 22 female (44%). The meanage was 23 year (ranged from 7 to 50). On histologicalexamination, there were 7 patients (14%) in group one, 29patients (58%) in group two, and 14 patients (28%) ingroup three. Serum IL-6 values gave true negative resultsin 6%, true positive results in 82%, false negative results in4%, and false positive results in 8%. We determined,therefore, in the present study the sensitivity, specificity,and accuracy of serum IL-6 were calculated as 95.34%,42.85%, and 88% respectively.Conclusion: Laboratory results should be considered to beintegrated within the clinical assessment. If used critically,IL-6 can provide surgeons with complementaryinformation in discerning the necessity for urgentoperation